Influence of Social Media Marketing, Word of Mouth, and Influencer Marketing on Brand Awareness: A Case Study of AT Koffie Lab Café - Bryan Budinata; Vern Christopher; Krisitan Agung Nugraha (JURNAL ILMIAH EDUNOMIKA, 2026)
Technological development has encouraged significant changes to marketing strategies within the culinary industry, particularly through utilization of social media, word of mouth from consumers, and collaborating with influencers. This study aims to analyze the influence of social media marketing, word of mouth, and influencer marketing on brand awareness at AT Koffie Lab Surabaya. This research employs a quantitative approach using a survey method by distributing surveys to consumers and potential consumers of AT Koffie Lab who are active users of social media. Data that has been collected are analyzed to determine the partial and simultaneous effects of the variables on brand awareness. The results are expected to provide insights of the effectiveness of the variables in enhancing brand awareness in café businesses. This research is expected to offer practical contributions for culinary business owners in designing more effective and efficient marketing strategies to improve businesses in the digital era.